System-Level Design Considerations for Carbon Nanotube Electromechanical Resonators. (5th November 2013) - Kauth, Christian; Pastre, Marc; Sallese, Jean-Michel; Kayal, Maher
Abstract : Despite an evermore complete plethora of complex domain-specific semiempirical models, no succinct recipe for large-scale carbon nanotube electromechanical systems design has been formulated. To combine the benefits of these highly sensitive miniaturized mechanical sensors with the vast functionalities available in electronics, we identify a reduced key parameter set of carbon nanotube properties, nanoelectromechanical system design, and operation that steers the sensor's performance towards system applications, based on open- and closed-loop topologies. Suspended single-walled carbon nanotubes are reviewed in terms of their electromechanical properties with the objective of evaluating orders of magnitude of the electrical actuation and detection mechanisms. Open-loop time-averaging and 1 ω or 2 ω mixing methods are completed by a new 4 ω actuation and detection technique. A discussion on their extension to closed-loop topologies and system applications concludes the analysis, covering signal-to-noise ratio, and the capability to spectrally isolate the motional information from parasitical feedthrough by contemporary electronic read-out techniques.